A high-voltage, long-pulse generator based on magnetic pulse compressor and Blumlein-type rolled strip pulse forming line. (1st July 2015) - Li, Song; Gao, Jing-Ming; Yang, Han-Wu; Qian, Bao-Liang
Abstract In this paper, a new technical scheme of high-voltage, long-pulse generator, mostly based on solid-state power devices, including magnetic pulse compressor, Blumlein-type rolled strip pulse-forming line (RSPFL) and inductive voltage adder (IVA), is proposed and investigated numerically and experimentally. The generator has potential advantages of high average power level, high repetitive rate capability, long lifetime, and long pulse achievability, which meet the requirements of military and industrial application of the pulsed power technology. Specifically, a two-stage magnetic pulse compressor was set up with iron-based amorphous cores. Total compression ratio of the device is approximately 12 and the achieved voltage efficiency is up to 92%. Low impedance, long-duration Blumlein-type RSPFL was established with characteristic impendence and electrical length of 3 Ω and 100 ns, respectively. Mylar film was selected as the solid-state dielectric. Increased by a four-stage IVA, typical quasi-square pulse was obtained with peak current of 2.3 kA and duration over 200 ns. As the resistance of the dummy load was measured to be 60 Ω, the peak voltage was approximately 138 kV. Experiments show reasonable agreement with numerical analysis.